Application of the Nature of Science in Elementary Science Learning During the Covid-19 Pandemic - Pramswari, Lungguh Puri; Widodo, Ari; Sujana, Atep; Sopandi, Wahyu (International Conference on Elementary Education, 2022)
This study aimed to analyze the application of the nature of science in high-grade elementary science learning and the obstacles faced by teachers and students during the Covid-19 pandemic. This study used a qualitative descriptive method to provide an overview of the application of the nature of science in elementary science learning during the Covid-19 pandemic. The subjects in this study comprised of 41 teachers and 127 high-grade students from various regions in Indonesia. The instrument used in this study was a questionnaire containing 29 statement items for teachers and 21 statement items for students with four answer choices namely always, often, sometimes, and never based on three indicators, namely (1) Science Product, (2) Science Process, (3) Science Attitude. Based on the results of the analysis, it is shown that the indicators of science product and science attitude have the highest percentages chosen by students with answers of always; meanwhile, the science process indicator has the highest percentages chosen by students and teachers for answer of sometimes. Therefore, it can be concluded that elementary science learning in high-grade during the Covid-19 pandemic did not run optimally due to the lack of application of the nature of science, especially the science process.